Psychological Intervention in Psychotic Crisis: a person-centered approach - TOSTES,Guilherme Wykrota (2021)
Abstract This article describes, theoretically analyzes, and exemplifies, through a fictitious vignette, a psychological intervention of a clinical nature, developed by psychologists in a tertiary mental health care hospital, as an alternative to conventional physical restraint in situations of acute psychotic crises. The theoretical framework adopted is Person-Centered Approach, developed by the North American psychologist Carl Rogers. The psychological intervention reveals the importance of an interpersonal relationship in the care of patients who are going through a psychotic crisis. The psychologist’s therapeutic posture includes the three attitudes advocated by Carl Rogers as necessary and sufficient to facilitate the process of resuming personal autonomy (congruence or authenticity, unconditional positive regard, and empathic understanding), in addition to confidence in the patient’s own actualizing tendency. The therapeutic strategy presented is a possible resource to be used to stabilize the person in crisis. These attitudes were initially proposed by Rogers and his team to develop and maintain a psychotherapeutic intervention process, but they also proved to be effective in the experience of Brazilian psychologists in relation to patients with severe mental disorders in acute crises.